Sex differences in severe acute malnutrition in children under 5 years in Zambia. - Gift C Chama; Situmbeko Liweleya; Lweendo Muchaili; Bislom C Mweene; Sydney Mulamfu; Lukundo Siame; Sepiso K Masenga (PLOS Global Public Health)
Severe acute malnutrition (SAM) is a critical public health issue, particularly in low and middle-income countries like Zambia, where it significantly contributes to under-five mortality. While general factors associated with SAM, including its overall burden, are well documented, the role of sex differences in correlates of SAM has not been thoroughly explored. Hence, this study aimed to examine sex differences in correlates of SAM by identifying key factors influencing malnutrition in males and females under five years, with particular attention to comorbid conditions such as Human Immunodeficiency Virus (HIV) and Tuberculosis (TB), which are known to complicate malnutrition in this population. We conducted a retrospective cross-sectional study utilizing data from 429 medical records of children aged 6 months to 5 years who were attended to at Livingstone University Teaching Hospital between 2020 and 2022. The median age at diagnosis for both males and females was 18 months, with interquartile ranges of 11-25 months and 12-24 months, respectively. Females had a higher prevalence of SAM (24.3%, n = 46) compared to males (19.58%, n = 47). TB was significantly associated with SAM in both males (AOR: 14.30, 95% CI: 2.08-98.5, p = 0.006) and females (AOR: 40.50, 95% CI: 4.83-340, p < 0.001), and the lymphocyte-to-monocyte ratio was also associated with SAM in males (AOR: 1.39, 95% CI: 1.05-1.83, p = 0.017) and females (AOR: 1.22, 95% CI: 1.00-1.49, p = 0.045). Additionally, comorbidities (AOR: 4.1, 95% CI: 1.13-14.90, p = 0.031) and age (AOR: 0.91, 95% CI: 0.85-0.97, p = 0.009) were associated with SAM in females, while these associations were not significant in males. Overall, females are more frequently diagnosed with SAM, most likely due to the presence of comorbidities such as TB and HIV. TB was found to be a critical risk factor for SAM in both sexes, highlighting the need for sex-specific interventions in the management of SAM.